WEBSITE QUALITY ANALYSIS AS A COMPANY INFORMATION MEDIA USING GTMETRIX AND LIGHTHOUSE METHODS - Kurnia Yahya; Muh. Radit; Ahmad Syaifullah Baihakki (STMIK Indonesia Banda Aceh, 2026)
A company website plays a crucial role as an information medium that provides profiles , services , and the latest information to the public . This study aims to evaluate the quality of the Galesong Group website (galesong.co.id) as an information medium using the GTmetrix and Google Lighthouse methods . The study used a quantitative descriptive approach by testing the website's homepage using both tools to obtain performance scores and Core Web Vitals metrics . The test results showed that the Performance score on Google Lighthouse was 58 ( moderate category ), while GTmetrix recorded a grade F with a Performance score of 25 % . Both tools consistently identified Largest Contentful Paint (LCP) and Cumulative Layout Shift (CLS) as the most critical issues , with LCP ranging from 2.5–4.5 seconds and CLS reaching 0.367, both exceeding the recommended threshold . The main factors causing these issues included excessive total page size ( 7.79 MB ) , unoptimized images , CSS resources that hinder rendering, and long- duration JavaScript tasks from third - party scripts such as live chat widgets . This study concludes that although the website scored well in the Best Practices category (92), significant optimization is still needed in image compression , JavaScript management , and layout stability to improve user experience and search engine visibility . These findings confirm that automated audit tools such as Lighthouse and GTmetrix are effective and complementary methods for evaluating the quality of a website as an information medium .